COMPARATIVE STUDY OF POST ISLAMISM BETWEEN PARTAI KEADILAN SEJAHTERA (PKS) WITH ADALET VE KALKINMA PARTISI (AKP) - Argenti, Gili (JWP (Jurnal Wacana Politik), 2018)
After the Arab Spring, political Islam was initially expected to contribute significantly to political developmentand democracy. In fact, it is far from expectations. The Islamist group failed to adapt to the democratic system,the conflict with the long-lasting secular group finally invited the military to intervene. While in other partsof the world two Muslim-majority countries, Indonesia and Turkey, political Islam can adapt to the valuesof western democracy. This paper is a comparative study of political parties that compare post Islamismbetween PKS (Indonesia) and AKP (Turkey). Two political parties that successfully adapt to liberalism. Thereare two dimensions of post Islamism compared. First, a comparison of pragmatic steps that PKS and AKPmake when facing a complex political reality. Second, the comparison of non-ideological strategies pursuedby PKS and AKP, when facing national elections. In this research used descriptive qualitative method throughthe literature data, that is data arranged in the form of documents related to the problem under investigation.Like books, newspapers, articles, and journals. Based on this research can be known that the step of politicalpragmatism conducted by PKS and AKP is a rational choice, when there is a shift in voter behavior ofIndonesia and when facing Kemalist secularist group in Turkey. The non-ideological strategy is carried outby PKS and AKP by campaigning on substantive issues, not discouraging the establishment of an Islamicstate (shariah formalism) with a focus on issues related to economic welfare and integration to the EU.